2020
DOI: 10.1111/cdev.13352
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Study of the Self‐Prioritization Effect in Children Between 6 and 10 Years of Age

Abstract: Self-biases are well described in adults but remain poorly understood in children. Here, we investigated in 6-10 year-old children (N = 132) the self-prioritization effect (SPE), a self-bias which reflects, in adults, the perceptual advantage for stimuli arbitrarily associated with the self as compared to those associated with other persons. We designed a child-friendly adaptation of a paradigm originally introduced in adults by Sui, He, and Humphreys (2012) in order to test whether the SPE also occurs in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
2
9
0
1
Order By: Relevance
“…The current study clarifies that the developmental trajectory for the iSRE is flat across childhood, supporting the findings of previous research (e.g., Cunningham et al, 2014;Dunbar et al, 2016;Maire et al, 2020). We now have four studies measuring the iSRE using the same concrete encoding task that demonstrate an age-invariant pattern from early to late childhood (Study 1, Study 2; Cunningham et al, 2014;Ross et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current study clarifies that the developmental trajectory for the iSRE is flat across childhood, supporting the findings of previous research (e.g., Cunningham et al, 2014;Dunbar et al, 2016;Maire et al, 2020). We now have four studies measuring the iSRE using the same concrete encoding task that demonstrate an age-invariant pattern from early to late childhood (Study 1, Study 2; Cunningham et al, 2014;Ross et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, Maire et al (2020) recently showed an age-invariant processing advantage for stimuli associated with self in middle childhood. In this study, children aged six to ten years learned pairings between referents (self, friend, stranger) and vacation spot images.…”
Section: Sre Developmentmentioning
confidence: 97%
“…With this, we not only replicated the standard SPE as observed in the previous literature ( Sui et al, 2012 ; Oakes and Onyper, 2017 ; Yankouskaya et al, 2017 ; Kim et al, 2019 ; Woźniak and Knoblich, 2019 ) but also extended the SPE in the older children and teenagers and showed that SPE remains robust across the developmental years. The observed bias for the newly learned self-association in the older children group is consistent with the previous work on SPE in younger children (6–10-year-old; Maire et al, 2020 ) and self-ownership studies, which show greater memory ( Cunningham et al, 2013 , 2014 ) and greater retention rate for the self-referent objects compared to others-referent objects in the early childhood years (3–6 year old; Axelsson et al, 2018 ). Our result also showed an overall decrease in the matching judgment response time with age, suggesting that 9–13-year-old children were, in-general, slower than teenagers and young adults.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Jiang et al (2019) showed a comparable self-advantage in the participants from the UK as well as Hong Kong (HK), suggesting that self-bias could be a universal phenomenon (however, HK participants show similar performance in the friend and stranger category; also see Zhu and Han, 2008 ). Furthermore, Maire et al (2020) recently reported SPE in younger children (6–10-year-old children), suggesting that SPE is a strong effect that starts very early. Taken together, recent literature suggests a vital role of newly acquired self-association on information processing wherein self-associated information is prioritized over that of a friend-, mother-, and stranger-associated information.…”
Section: Introductionmentioning
confidence: 99%
“…There is rich evidence showing that one's name, as well as images of one's face are processed faster and more accurately than other comparable stimuli (Alexopoulos et al 2012;Alzueta, et al 2019). This effect seems to be in place early in development, with children between 6 and 10 years of age already showing self-prioritization (Maire et al 2020). More recently, it has been demonstrated that a similar effect can be reliably observed also for non-familiar stimuli (e.g.…”
Section: Discussionmentioning
confidence: 94%